A task allocation model for minimising system cost and maximising reliability of distributed computing system. (2018) - Kumar, Harendra; Chauhan, Nutan Kumari; Yadav, Pradeep Kumar
A distributing computing system (DCS) presents a platform consisting of multiple computing nodes connected in some fashion to which various task of a parallel application could be assigned. Effective task allocation is an essential phase to obtain the optimal cost and reliability of DCS. This paper addressed a new heuristic model of allocating the tasks onto multiple processors in order to achieve optimal cost and optimal reliability of the system. Costs have been taken as fuzzy numbers, which are more realistic and general in nature. Fuzzy program is transformed into crisp one by using the method of defuzzification. A membership function is developed to transform the communication cost in unit interval [0, 1]. Clusters of tasks have been built on the basis of their membership values. To present the effect of the proposed model, it has been implemented on various numerical examples and compared with other existing method related to this field.